Case Marking Variation in Heritage Slavic Languages in Toronto: Not So Different. (13th May 2019) - Łyskawa, Paulina; Nagy, Naomi
Abstract: We examined case‐marking variation in heritage Polish, Russian, and Ukrainian. Comparing heritage to homeland Polish and Ukrainian speakers, we found only a few types and a few tokens of systematic distinction between heritage and homeland varieties. A total of 6, 291 instances of nouns and pronouns were extracted from transcribed conversations with 62 speakers. Comparing normative forms to observed forms in logistic regression analyses showed that the form of the nominal and the case selector have significant effects on the rate of match between normative and observed forms, while declension does not. Most mismatches in the heritage data were replaced by the nominative, a pattern which is also occasionally found in homeland speech. The second most frequent pattern is genitive–accusative mismatch in specific contexts, in both heritage and homeland speech. Importantly, no significant differences between homeland and heritage speakers emerged, with 8% mismatch attested in the heritage and 2% in homeland data. Abstract :